2012
DOI: 10.1002/asna.201111645
|View full text |Cite
|
Sign up to set email alerts
|

Power spectral distribution of the BL Lacertae object S5 0716+714

Abstract: Observational data in the BVRI bands of the variable BL Lacertae object S5 0716+714 are discussed from the point of view of its power spectral distribution (PSD). A model of the type P (f ) = βf −1 1 + (f/δ) α−1 −1 + γ is fitted to the data for four null hypothesis and the Bayesian p parameter for the fits is calculated. Spectral slopes with values ranging from 1.083 to 2.65 are obtained, with medium values for each band of αB = 2.028, αV = 1.809, αR = 1.932 and αI = 1.54 respectively. These values confirm con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This is a consequence of the fact that SOC may be an underlying principle in Nature, as the initial intuition of [5] stated. Examples in astrophysics include organization of plasma in accretion discs [28] to explain observational data such as those discussed in [29], axion clouds around black hole [30], solar flares [9,14,17,21]. [39] have analyzed GRB X-Ray data, and they did find that all observational results can be fitted into a framework based on a stochastic pulse avalanche model running in a near-critical regime.…”
Section: Introductionmentioning
confidence: 99%
“…This is a consequence of the fact that SOC may be an underlying principle in Nature, as the initial intuition of [5] stated. Examples in astrophysics include organization of plasma in accretion discs [28] to explain observational data such as those discussed in [29], axion clouds around black hole [30], solar flares [9,14,17,21]. [39] have analyzed GRB X-Ray data, and they did find that all observational results can be fitted into a framework based on a stochastic pulse avalanche model running in a near-critical regime.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with the statistical properties of observational data for a BL Lac, e.g. analysed in [24], is good.…”
Section: Resultsmentioning
confidence: 77%
“…, a PSD analysis performed on IDV data in the BVRI bands has shown that α varied between approximately −1.5 and −2.7 for that set of data [51].…”
Section: Comparison With Agn Idv Datamentioning
confidence: 94%